Feminist Biblical Interpretation through an Intersectional Lens: Diverse Developments in Theory, Methodology, and Practice (Journal for the Study of Religion and History (JSRH), 2025)
This paper traces the development of feminist biblical interpretation from its marginal beginnings to its current position as a mainstream academic approach. It examines the field’s evolution through four historical phases: early enlightenment (late 19th -mid 20th century), systematic development (1960s-1980s), theoretical diversification (1990s-early 2000s), and contemporary intersectional analysis. It explores key theoretical frameworks, methodological innovations, and significant contributions that have shaped this field. Special attention is given to recent developments in intersectionality and global-south perspectives, which have profoundly enriched biblical interpretation through diverse cultural lenses. The paper also addresses the impact of digital humanities technologies on biblical scholarship. While highlighting feminist biblical criticism’s achievements in challenging patriarchal interpretations and recovering overlooked female voices, the paper acknowledges ongoing challenges, including methodological debates and tensions with traditional approaches. It concludes by emphasizing feminist biblical interpretation’s continued relevance and potential for promoting social justice.
Keywords: Feminist Biblical Interpretation, Gender and Religion, Hermeneutics, Intersection¬ality, Global-South Perspectives